Satellite Trajectory and Types of Orbits (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The main goal of studying the above topic is to get acquainted with the general information currently learned about the trajectories of satellites and the types of their orbits. To study the general characteristics of the orbit, how satellites move in each type of orbit and for what purpose. To evaluate each orbit from a scientific point of view and from an economic point of view, depending on the emerging benefits in different fields.